Supratentorial Pediatric Midline Tumors and Tumor-like Lesions: Clinical Spectrum, Natural History and Treatment Options - Luca Paun; Alexandre Lavé; Gildas Patet; Andrea Bartoli (MDPI AG, 2022)
Childhood Central Nervous System tumors account for 25% of all pediatric tumors. Large availability and broadening of indications to imaging has made incidental findings more common. Among these, midline lesions have different clinical relevance depending on their intrinsic pattern of behaviour and on their specific location. In this narrative review we describe the natural history and treatment options of midline lesions in children.